PENYIMPANAN SPERMATOZOA PADA SUHU PRESERVASI DAN BERBAGAI PENGENCER SEMEN TERHADAP DAYA TAHAN HIDUP SPERMATOZOA - Desi Septiani; E. Mulyati Effendi; - Moerfiah (Universitas Pakuan, 2017)
The purpose of this research is to know the quality of diluent which is stored at room temperature and temperature of preservation to survival of spermatozoa, to know the temperature of cement storage to survival of spermatozoa and to know the type of cement diluent material to survival of spermatozoa. The study used local sheep cement. The design used was Randomized Block Design (RAK) Factorial pattern with 2 treatment of storage temperature ie S1 = room temperature; S2 = preservation temperature; and with 4 diluent treatment: P1 = yolk citrate; P2 = skim milk; P3 = liquid milk; P4 = tris of soybeans. The observed variables were the macroscopic and microscopic cement quality prior to dilution, the progressive movement of sperm from each diluent and the progressive movement of sperm at each storage temperature. The administration of yolk citrate diluents affects the survival of spermatozoa compared with other diluents (P 0.05). The preservation temperature gives optimum results in suppressing the rate of decline in survival of spermatozoa (P 0.05). Giving yolk citrate stored at a preservation temperature is apparent in maintaining the survival of spermatozoa with 55% motility for three days.Â Keywords: survival, spermatozoa, cement diluents, storage temperature